An analysis of shooting accuracy towars archery athlete´s arm length, arm strength, and body mass index (a study of KONI Bandung District, Archery Division) - Noor, G. Z. (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2023)
Abstract Background. Accuracy in archery is the ability to achieve (point) against the target or Target Face when the arrows are out of the bow using a high level of consentration in carrying out a series of shooting techniques. Based on many numbers of arrow athletes who won the championship by balancing their body balance and maintaining their stamina.